Five-year follow-up of transvenous and epicardial left ventricular leads: experience with more than 1000 leads. (21st October 2019) - Burger, Heiko; Pecha, Simon; Hakmi, Samer; Opalka, Bastian; Schoenburg, Markus; Ziegelhoeffer, Tibor
Abstract: OBJECTIVES: Transvenous coronary sinus leads are considered to be the gold standard for cardiac resynchronization therapy (CRT). However, in patients with abnormal coronary vein anatomy, the epicardial leads can be an alternative. Data comparing durability and performance of these 2 lead types are limited. In order to provide clarity, we investigated patients receiving CRT system in our centre. METHODS: One thousand and fifty-three consecutive patients scheduled for CRT implantation were retrospectively analysed. From these, 895 received transvenous coronary sinus and 158 epicardial left ventricular (LV) leads. Lead-specific as well as LV functional parameters have been evaluated in 60 months' follow-up. RESULTS: Technical characteristics (pacing threshold, impedance and sensing) of both lead types remained stable during the whole observation period. Whereas an early revision (<6 month) was noted in 5.4% of transvenous leads, no reintervention has been necessary for epicardial leads. During the 5-year observation period, a lead revisions rate of 10.2% for transvenous leads and 1.9% for epicardial leads were detected. Regarding CRT efficacy, excellent results were achieved for both electrode types. In both groups, a statistically significant reduction of New York Heart Association class (2.85–2.13 and 2.96–2.09), increase in left ventricular ejection fraction (24.6–32.6% and 27.2–34.6%), reduction of left ventricular end-systolic diameter/left ventricular end-diastolic diameter and reduction in degree of mitral valve insufficiency could be observed over the time. CONCLUSIONS: Our data demonstrate safety and functional efficacy of both transvenous and epicardial leads. Moreover, in long-term follow-up, a commendable durability and performance were found for both lead types. Thus, epicardial leads represent a good alternative when transvenous implantation fails.